Cinema de mulheres em Sergipe: um mapeamento de filmes e trajetórias de cineastas (1974 – 2023) - Passos, Manoela Veloso (2023)
This work produces and analyzes in a qualitative and quantitative way data on audiovisual productions carried out in Sergipe with women in the direction, in order to map and make visible such production, of historical and cultural importance for the state. The study is based on exploratory and documentary research in different sources of information, the main ones being the film festivals in the state (FENACA, Curta-SE, Sercine, EGBÉ and FestCine) and the two journalistic portals (Aracaju Magazine and Infonet), for the construction of a film catalog, then analyzing the set of films according to their cinematographic genre and their themes, especially those related to women and Sergipe. Also presented are the trajectories of the pioneers – Maria Anamira Batalha Amado Neta and Ilma Fontes -, of some filmmakers who did not continue their careers as directors in Sergipe – Marivone Vieira, Everlane Moraes and Grazielle Ferreira – and of filmmakers working in the state – Gabriela Calda, Jade Moraes, Moema Pascoini, Luciana Oliveira, Manoela Veloso Passos and Caroline Mendonça Considering the proposed gender perspective, a feminist analysis of cinema is used as a theoretical reference based on the authors Ana Catarina Pereira (2016), Karla Holanda (2015, 2017 and 2019), Marina Cavalcanti Tedesco (2017 and 2022), in addition to issues related to audiovisual preservation in Brazil.